2022
DOI: 10.3389/fphar.2022.922484
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine Confers Protection Against Myocardial Ischemia Reperfusion Injury by Preventing Oxidative Stress, Cellular Apoptosis, and Inflammation

Abstract: Sinomenine (SIN), an alkaloid extracted from the root of S. acutum. sinomenine, has been shown to have antiarrhythmic, antioxidant, and anti-inflammatory effects in myocardial ischemia-reperfusion injury (MIRI) ex vivo. In this study, we investigated the cardioprotective effects of SIN in an in vivo mouse model of MIRI. Adult male C57BL/6J mice received SIN (80 mg/kg) for 5 days and underwent 30 min of percutaneous occlusion of the left anterior descending artery (LAD) followed by 24 h of reperfusion. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…20 Sinomenine confers protection against hepatic 17 and myocardial I/R injury by preventing oxidative Stress, cellular apoptosis, and inflammation. 33 …”
Section: Discussionmentioning
confidence: 99%
“…20 Sinomenine confers protection against hepatic 17 and myocardial I/R injury by preventing oxidative Stress, cellular apoptosis, and inflammation. 33 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, the HIF-1α/NF-κB signaling pathway was found to play a key role in the protective effect of DKHP on the heart. NF-κB is a key protein of the entire inflammatory family [ 29 ], a typical signaling pathway [ 30 ] responsible for the process of inflammatory infiltration and inhibition of cell survival. Phosphorylated IKβ can promote the release of NF-κB, which enters the nucleus and activates the expression of inflammatory genes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyocytes express high levels of endoplasmic reticulum stress-related signaling proteins, including transcription factor 6 (ATF6), C/EBP homologous protein (CHOP), glucose regulatory protein 78 (GRP78), etc. Treatments that Inhibit the signaling of endoplasmic reticulum stress can effectively reduce the rate of cell death in conditions like myocardial ischemiareperfusion injury (61)(62)(63)(64). Key cellular events in the pathogenesis of MIRI are summarized in Figure 1.…”
Section: Endoplasmic Reticulum Stressmentioning
confidence: 99%